Bilateral Vision Loss after Delivery in Two Cases: Severe Preeclampsia and HELLP Syndrome - Çelik, Gökhan (Turk J Ophthalmol, 2015)
Two patients with no symptoms of hypertension in their medical history before pregnancy were referred to the obstetrics emergency clinic with hypertension and visual complaints. After physical examination and laboratory tests, one of the patients was diagnosed with severe preeclampsia while the other was diagnosed with HELLP syndrome (Hemolysis-Elevated Liver enzymes-Low Platelets). Ocular examinations were performed after delivery due to the patients’ worsening visual complaints. The severe preeclamptic patient showed bilateral serous retinal detachment (SRD) while the patient with HELLP syndrome showed bilateral macular hemorrhage. Systemic blood pressure control was advised. The patients’ ocular findings and visual acuities improved in the follow-up periods. SRD and macular hemorrhage can be observed in patients with preeclampsia and HELLP syndrome as a result of the disruption of retinal and choroidal vasculature.